(untitled) (Bangladesh Journal of Botany, 2025)
Globally, breeding programs focus on selecting stable genotypes to ensure consistent crop yields across varying climatic conditions. In this study, seven mustard genotypes (Brassica juncea) were evaluated at three environments (early, mid and late sowing) on ten yield-contributing traits to determine the best genotypes and their optimal growing periods. Significant differences among the three environmental conditions were noted through a combined analysis of variance. The overall seed yield performance at late sowing was considerably lower than the early and mid-sowing conditions. The genotype ranking through AMMI and GGE biplots revealed that Daulat, BARI-11 and BARI-16 were the highest yield-producing stable genotypes across the environments. Additionally, correlation coefficient analysis indicated seed yield was positively correlated with siliquae per plant, thousand-seed weight and harvest index under all the environmental conditions, providing a sound basis for future mustard breeding programs. Bangladesh J. Bot. 54(4): 957-966, 2025 (December)